Policy statement on tertiary education for Aborigines and Torres Strait Islanders - Australia. National Aboriginal Education Committee (Canberra : Australian Government Publishing Service, 1986)
Outlines general issues; resource needs and programs; participation rates - lists tables indicating enrolments in higher education and hypothetical progression at tertiary level; recommendations.
AGPS cat. no. 8611712.
Includes bibliographical references.
Keywords: Aboriginal Australians -- Education -- Government policy; Torres Strait Islanders -- Education -- Government policy; Education - Grants and finance; Education - Tertiary; Australia